(3TQM ThGgO SjHhjgs - (3YeQh Hf YKeGf Hf bfHQ GdMGQKj, SjHhjg, CHh HTQ , J (B180 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg hGfTO HYOg hgh GdTGgO GdSGOS YTQ HYO GdeGFJjf hgh ef S KdGKhf ddgLQ MhdkG cGedkG Ydi Gfg aUd HGdeLQhQ VQhQI Hjf GdJejjR hgh MhdkG s
(3BNQgG (B:s
(3hBNQ GdehLhO efg (B: (3hGfTOg HYOg hgh GdTGgO GdYTQhf HYO GdGQHYeGFI hGddPG dhTGA dcfJ UNQkG Ch LHdkG hYdeg YfO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B10s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs